RbSnX3 (X = Cl, Br, I): promising lead-free metal halide perovskites for photovoltaics and optoelectronics. Issue 12 (7th March 2022) - Rahman, Md. Habibur; Jubair, Md.; Rahaman, Md. Zahidur; Ahasan, Md. Shamim; Ostrikov, Kostya (Ken); Roknuzzaman, Md
Abstract : This work summarizes that RbSnX3 (X = Cl, Br, I) exhibits remarkable ductility and absorption in the ultraviolet (UV) region of the electromagnetic spectrum compared to those of CsBX3 (B = Ge, Sn, Pb; X = Cl, Br, I) metal halide perovskites. Abstract : Lead (Pb) free metal halide perovskites by atomistic design are of strong interest to photovoltaics and optoelectronics industries because of the pressing need to resolve Pb-related toxicity and instability challenges. In this study, structural, mechanical, electronic, and optical properties of Pb-free RbSnX3 (X = Cl, Br, I) perovskites have been evaluated by using ab initio density functional theory (DFT) calculations. The computed elastic constants suggest that the Rb-based halide perovskites are mechanically stable and highly ductile, making them suitable as flexible thin films in optoelectronic devices. Besides, the investigated electronic band structures reveal that the RbSnX3 compounds are direct bandgap semiconductors, suitable for photovoltaic and optoelectronic applications. Furthermore, several optical parameters such as dielectric functions, reflectivity, photon absorptions, refractive index, optical conductivity, and loss functions have been investigated and the results predict the excellent optoelectronic efficiency of RbSnX3 . Also, the computed mechanical and optical properties of RbSnX3 (X = Cl, Br, I) have been compared with the previously studied CsBX3 (B = Ge, Sn, Pb; X = Cl, Br, I) phases, revealing that the Rb-based perovskites are extremely ductile and possess excellent light absorption and optical conductivity compared to the Cs-based perovskites. Importantly, RbSnI3 shows superior ductility, absorption coefficient, and optical conductivity compared to the CsBX3 (B = Ge, Sn, Pb; X = Cl, Br, I) perovskites. Superior absorption at the ultraviolet region of RbSnI3 holds great promise of this perovskite to be used in next-generation ultraviolet photodetectors.